Preparation and evaluation of tamsulosin hydrochloride sustained-release pellets modified by two-layered membrane techniques - Jingmin Wang; Yinghua Sun; Bo Li; Rui Fan; Bing Li; Tengrui Yin; Ling Rong; Jin Sun (Elsevier, 2015)
The aim of the present study was to develop tamsulosin hydrochloride sustained-release pellets using two-layered membrane techniques. Centrifugal granulator and fluidized-bed coater were employed to prepare drug-loaded pellets and to employ two-layered membrane coating respectively. The prepared pellets were evaluated for physicochemical characterization, subjected to differential scanning calorimetry (DSC) and in vitro release of different pH. Different release models and scanning electron microscopy (SEM) were utilized to analyze the release mechanism of Harnual® and home-made pellets. By comparing the dissolution profiles, the ratio and coating weight gain of Eudragit® NE30D and Eudragit® L30D55 which constitute the inside membrane were identified as 18:1 and 10%-11%. The coating amount of outside membrane containing Eudragit® L30D55 was determined to be 0.8%. The similarity factors (f2) of home-made capsule and commercially available product (Harnual®) were above 50 in different dissolution media. DSC studies confirmed that drug and excipients had good compatibility and SEM photographs showed the similarities and differences of coating surface between Harnual® and self-made pellets before and after dissolution. According to Ritger-Peppas model, the two dosage form had different release mechanism.